TICs 167692429 and 220397947: the first compact hierarchical triple stars discovered with TESS. Issue 4 (18th February 2020) - Borkovits, T; Rappaport, S A; Hajdu, T; Maxted, P F L; Pál, A; Forgács-Dajka, E; Klagyivik, P; Mitnyan, T
ABSTRACT: We report the discovery and complex analyses of the first two compact hierarchical triple star systems discovered with TESS in or near its southern continuous viewing zone during Year 1. Both TICs 167692429 and 220397947 were previously unknown eclipsing binaries, and the presence of a third companion star was inferred from eclipse timing variations exhibiting signatures of strong third-body perturbations and, in the first system, also from eclipse depth variations. We carried out comprehensive analyses, including the simultaneous photodynamical modelling of TESS and archival ground-based WASP light curves, as well as eclipse timing variation curves. Also, for the first time, we included in the simultaneous fits multiple star spectral energy distribution data and theoretical PARSEC stellar isochrones, taking into account Gaia DR2 parallaxes and catalogued metallicities. We find that both systems have twin F-star binaries and a lower mass tertiary star. In the TIC 167692429 system, the inner binary is moderately inclined ( i mut  = 27°) with respect to the outer orbit, and the binary versus outer (triple) orbital periods are 10.3 versus 331 d, respectively. The mutually inclined orbits cause a driven precession of the binary orbital plane that leads to the disappearance of binary eclipses for long intervals. In the case of TIC 220397947, the two orbital planes are more nearly aligned and the inner versus outer orbital periods are 3.5 and 77 d, respectively. In the absence of radial velocity observations, we were unable to calculate highly accurate masses and ages for the two systems. According to stellar isochrones TIC 167692429 might be either a pre-main sequence (MS) or an older post-MS system. In the case of TIC 220397947, our solution prefers a young pre-MS scenario.